2007
DOI: 10.2215/cjn.02250507
|View full text |Cite
|
Sign up to set email alerts
|

Home Blood Pressures Are of Greater Prognostic Value than Hemodialysis Unit Recordings

Abstract: Background and objectives: Although ambulatory BP recordings are found to be superior to dialysis unit recordings in predicting outcomes, ambulatory BP are difficult to obtain in the day-to-day treatment of hemodialysis patients. Home BP agree well with ambulatory BP, but the prognostic significance of home BP recordings is unknown in hemodialysis patients. This study ascertained the role of home BP in predicting all-cause and cardiovascular mortality.Design, setting, participants, & measurements: A prospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
200
0
7

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 224 publications
(215 citation statements)
references
References 28 publications
8
200
0
7
Order By: Relevance
“…We used ambulatory BP as a reference standard because ambulatory BP recording is an accurate estimate of the arterial pressure and shares a stronger relationship with all-cause mortality compared with BPs obtained in the dialysis unit (25). Not only can ambulatory BP provide a better mean estimate of arterial pressure over the interdialytic period, recent studies using ambulatory BP monitoring have disclosed that systolic BP increases by approximately 1 mmHg every 4 hours, and diastolic BP increases by 1 mmHg every 8 hours (26).…”
Section: Discussionmentioning
confidence: 99%
“…We used ambulatory BP as a reference standard because ambulatory BP recording is an accurate estimate of the arterial pressure and shares a stronger relationship with all-cause mortality compared with BPs obtained in the dialysis unit (25). Not only can ambulatory BP provide a better mean estimate of arterial pressure over the interdialytic period, recent studies using ambulatory BP monitoring have disclosed that systolic BP increases by approximately 1 mmHg every 4 hours, and diastolic BP increases by 1 mmHg every 8 hours (26).…”
Section: Discussionmentioning
confidence: 99%
“…Mitra et al measured BP in hemodialysis patients at arrival to the dialysis unit, after 10 min of rest in a quiet room, and at other time points in relationship to dialysis (17). The authors reported that the BP on arrival to the hemodialysis unit (19). BP increases over the interdialytic period most likely because of accumulation of volume and uremic toxins (20 -23).…”
Section: Discussionmentioning
confidence: 99%
“…However, it would be premature to discontinue home BP monitoring; home BP is associated with left ventricular hypertrophy (26) and mortality in hemodialysis patients (19), relationships that are yet to established for intradialytic BP recordings. Nonetheless, BP measurements obtained during dialysis appear to contain a larger amount of diagnostic information than what is apparent in predialysis and postdialysis BP measurements alone.…”
Section: Discussionmentioning
confidence: 99%
“…In dialysis patients, home BP carries better prognostic impact when compared to recordings in the dialysis unit. Systolic home BP of 115-145 mmHg is associated with the best prognosis in HD patients [86]. Renin-Angiotensin-system (RAS) blockers stimulate Klotho gene expression in CKD patients.…”
Section: Management Of Traditional Risk Factorsmentioning
confidence: 99%